The impact of adoption of artificial pollination technology in cocoa production: Evidence from Ghana - Wongnaa, Camillus Abawiera; Apike, Isaac Akurugu; Babu, Suresh Chandra; Awunyo-Vitor, Dadson; Kyei, Afrane Baffour (Elsevier, 2021)
This study analyzed the impact of adoption of artificial pollination on productivity, income, poverty and food security among cocoa farmers in Ghana. Primary data was collected from 206 cocoa farmers drawn through a multi-stage sampling technique and analyzed using Propensity Score Matching. The study revealed that households who adopted artificial pollination had improvements in their productivity, income, poverty situation, and food security. It was also revealed that adopters increased their productivity by close to 15.34% on average, earned between GH₵ 2756.84 to GH₵ 11074.38 more on average in terms of income, reduced their poverty by an average of between 0.83% and 3.53%, and finally, improved their food security by approximately 3% compared to non-adopters. Leveraging on the positive impact of adoption of artificial pollination, policymakers should take steps in implementing artificial pollination to help increase the yield of Ghana’s cocoa.